Profile of congenital malformations in a regional hospital in Paraná (Research, Society and Development, 2024)
Congenital malformations are changes in the body, both physiological and structural, that affect quality of life and can even progress to death. They originate during intrauterine life and can cause maternal-fetal suffering throughout pregnancy, in addition to complications during childbirth. This study aimed to characterize the profile of congenital malformations in a regional hospital in Paraná and relate the outcome to maternal variables and neonatal characteristics. This is a descriptive, explanatory, documentary, cross-sectional, retrospective, and quantitative research using information obtained through medical records of newborns and their respective mothers diagnosed with congenital malformation before or after birth, between 2023 and the first half of 2024. The outcome variable was dichotomized (hospital discharge x death) and associated with maternal sociodemographic variables and neonatal characteristics, using the chi-square test, accepting significance values of 5% (p-value